2015
DOI: 10.1097/ijg.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure During Robotic-assisted Laparoscopic Procedures Utilizing Steep Trendelenburg Positioning

Abstract: Significant elevations of IOP are experienced during robotic surgery utilizing sTBURG positioning in patients with healthy eyes, and we recommend a multidisciplinary approach in determining potential risk to those with known ocular disease who are candidates for these procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 19 publications
3
24
1
Order By: Relevance
“…To the best of our knowledge, the present study was the first and largest prospective study to evaluate IOP and visual field sensitivity during RALP in the patients with ocular diseases. We showed that IOP significantly increased during TP in RALP in a time‐dependent manner, as previously described . Regarding the degree of elevation of IOP, at 3 h after TP, glaucomatous patients showed significantly lower IOP change, partly because of perioperative ophthalmic drops to maintain IOP within the normal range.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…To the best of our knowledge, the present study was the first and largest prospective study to evaluate IOP and visual field sensitivity during RALP in the patients with ocular diseases. We showed that IOP significantly increased during TP in RALP in a time‐dependent manner, as previously described . Regarding the degree of elevation of IOP, at 3 h after TP, glaucomatous patients showed significantly lower IOP change, partly because of perioperative ophthalmic drops to maintain IOP within the normal range.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, several prospective clinical studies have been carried out to evaluate the effects on visual function in patients undergoing RALP . However, most studies excluded patients with pre‐existing ocular diseases, and included healthy patients who were favorable for RALP.…”
Section: Introductionmentioning
confidence: 99%
“…31 Intraocular pressure assessed in patients with head-down (Trendelenburg) surgical positioning has been found to increase, however, retinal nerve fiber layer thickness measured with optical coherence tomography does not appear to be altered in patients with vision impairments after surgery. 32, 33 Similarly, no clinically relevant findings were found during 14 day exposure to −6° HDT bed rest, 34 whereas 70 day −6° HDT bed rest could provoke an increase in the superior, nasal, and inferior peripapillary retinal thickness. 35 …”
Section: Discussionmentioning
confidence: 98%
“…Many of the studies highlighting POVL and markedly elevated IOP changes (reaching glaucomatous range) after laparoscopic surgery had been performed with steep Trendelenburg position or in prolonged procedures. 1214,19,21,22,24,25 Mondzelewski et al 22 observed a significantly elevated IOP in patients undergoing robot-assisted laparoscopic procedures in steep Trendelenburg position compared with IOP in those undergoing laparoscopy or open procedures in a horizontal position, further highlighting the role of positioning over and above that of pneumoperitoneum in significant IOP elevations. A recent study performed among patients undergoing laparoscopic colorectal surgery showed greater IOP elevation in both eyes of patients in Trendelenburg position during the surgical procedure, but found no substantial difference between the Trendelenburg and non-Trendelenburg group when IOP was measured 48 hours after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1518 With this in mind, in many studies, researchers have investigated the relationship between IOP changes during laparoscopy and different anaesthetic agents employed, whereas few have investigated the role of steep Trendelenburg position on IOP changes. 1922 The changes in IOP with normal Trendelenburg and reverse Trendelenburg positions have not been fully investigated. We sought therefore to evaluate the changes in IOP with such changes in patient position during laparoscopic surgeries.…”
Section: Introductionmentioning
confidence: 99%